THE EFFECT OF INFLUENCER MARKETING, VIRAL MARKETING AND CUSTOMER ENGAGEMENT ON PURCHASE INTENTION AT BLOODS STORE IN PURWOKERTO - Ramadhan, Muhammad; Astuti, Herni Justiana; Rahmawati, Erny; Ikhsani, Mastur Mujib (LPPM STIE Muhammadiah Bandung, 2024)
This research investigates the multifaceted influence of contemporary marketing methodologies, namely influencer marketing, viral marketing, and customer engagement, on consumers' purchase intentions. This research used SmartPLS statistical analysis tool version 3.0. This research uses an online questionnaire with a total of 150 respondent from students of the Faculty of Economics and Business at Jenderal Soedirman University, University of Muhammadiyah Purwokerto, and State Islamic University Prof. KH. Saifuddin Zuhri Purwokerto that have purchase intention in Blood Store Purwokerto. Based on the findings of this research, it shows that influencer marketing, viral marketing, and customer engagement has a positive and significant impact on the purchase intention. By understanding the synergistic effects of these marketing approaches, businesses can strategically tailor their campaigns to optimize customer engagement and enhance purchase intentions, ultimately fostering greater success in today's competitive market landscape.This research investigates the multifaceted influence of contemporary marketing methodologies, namely influencer marketing, viral marketing, and customer engagement, on consumers' purchase intentions. This research used SmartPLS statistical analysis tool version 3.0. This research uses an online questionnaire with a total of 150 respondent from students of the Faculty of Economics and Business at Jenderal Soedirman University, University of Muhammadiyah Purwokerto, and State Islamic University Prof. KH. Saifuddin Zuhri Purwokerto that have purchase intention in Blood Store Purwokerto. Based on the findings of this research, it shows that influencer marketing, viral marketing, and customer engagement has a positive and significant impact on the purchase intention. By understanding the synergistic effects of these marketing approaches, businesses can strategically tailor their campaigns to optimize customer engagement and enhance purchase intentions, ultimately fostering greater success in today's competitive market landscape.